Nursing Students Perception to Stress during Clinical Training at King Abdulaziz University - Samira Ahmed El-senany, Dalal Abdu Hakami, Sabah Mahmmoud Mahran, (Social Science Learning Education Journal, 2017)
The clinical training is a vital part of nursing curriculum, as most of the collegeâs time is spent in the clinical training. Stress is one of the important factor that may influence studentsâ learning, especially in clinical settings. Aim of this study is to investigate nursing studentsâ perception to stress during clinical training at King Abdulaziz University. Design: Quantitative descriptive design was implemented. Setting: Â Study was conducted in two medical departments; surgical (male and female) wards; outpatient clinic and day care unit at King Abduaziz University Hospital. Sample: Total studied sample 94 of second year nursing students at nursing faculty. Result: The findings revealed that slightly above two- third of the studied sample 69.15% complain stress because of unfamiliar with medical history and terms. And 86.38% were worried about poor grades, while approximately two- third (63.19%) of the studied sample expressing that dullness and inflexible clinical practice affect their family/social life. However, 70.32%Â 70.32%Â were anxious because they feel that they were unable to reach their teacher and staff expectations in the clinical training, while approximately two- third of them (66 % ) mentioned that they felt depress and miserable if they received negative criticism from their teachers and 71.49%Â were seeing a discrepancy between theory and practice .Conclusions & Recommendation: The results concluded that some stressors sources are related to academic study such as worrying about their grades, patients diagnosis overload of homework and assignments, further researches are recommended, andÂ to provide an academic guidance is recommend . Key words: StressÂ , stressorsÂ ,Â clinical training , nursing student.